Determinants of Technology Acceptance among Older Adults in Malaysia - Joshua Teck Khun Loo; Jie Jeng Chang; Sima Ahmadpour; Sumiko Chun Yi Cheng; Kock Lim Tan (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study examines elderly Malaysians’ intention to use QR ordering through the Unified Theory of Acceptance and Use of Technology, focusing on ease of use, performance expectancy, and social influence. A survey was analysed using partial least squares structural equation modelling. Diagnostics indicated acceptable univariate normality with some multivariate non normality, and checks for common method variance were satisfactory. The measurement model met accepted reliability and validity standards. In the structural model, performance expectancy and ease of use both showed positive effects on behavioural intention, while social influence was not a significant driver. The importance performance map identified performance expectancy as the most influential driver of intention and ease of use as the next most influential, both with room for further enhancement, whereas social influence showed limited importance. Findings suggest that older adults form intention when the system clearly delivers benefits such as faster and more convenient ordering and is simple to operate. Practically, providers should highlight tangible benefits, streamline the journey, and offer clear guidance at the point of use. Limitations include a single service context, a cross sectional design, and reliance on self reported intention. Future research should test causal pathways and examine mediators and moderators such as recognition of benefits, education, and dining context.